2020
DOI: 10.3399/bjgp.2020.0967
|View full text |Cite
|
Sign up to set email alerts
|

Changing media depictions of remote consulting in COVID-19: analysis of UK newspapers

Abstract: Background: Remote consulting was introduced quickly into UK general practice in March 2020 as an emergency response to Covid-19. In July 2020, ‘remote-first’ became long-term government policy. Aim: To explore how this change was portrayed in national newspapers and how depictions changed over time. Design and setting: We undertook a thematic analysis of newspaper articles referring to remote GP consultations from two time periods: March-May 2020 and July-August 2020. Method: Articles were identified through,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…22 Guidance was rapidly issued on when certain types of consultation may be most appropriate 6 and subsequently there has been reflection on the innovations that should be retained post-pandemic, 20 including evidence of emerging narratives in the media that are more critical of the trade-offs entailed by a permanent shift to remote consultations as the default. 23 Our findings corroborate those of Sharma et al, who conducted an online survey of GPs and practice managers in the East Midlands during May and June 2020 to explore how practices were coping with the pandemic. 12 They found practices implementing a similar range of measures, to both buildings and processes, to make face-to-face contact possible.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…22 Guidance was rapidly issued on when certain types of consultation may be most appropriate 6 and subsequently there has been reflection on the innovations that should be retained post-pandemic, 20 including evidence of emerging narratives in the media that are more critical of the trade-offs entailed by a permanent shift to remote consultations as the default. 23 Our findings corroborate those of Sharma et al, who conducted an online survey of GPs and practice managers in the East Midlands during May and June 2020 to explore how practices were coping with the pandemic. 12 They found practices implementing a similar range of measures, to both buildings and processes, to make face-to-face contact possible.…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…21 Guidance was rapidly issued on when certain types of consultation may be most appropriate 6 and subsequently there has been re ection on the innovations that should be retained post-pandemic, 19 including evidence of emerging narratives in the media that are more critical of the trade-offs entailed by a permanent shift to remote consultations as the default. 22 Our ndings corroborate those of Sharma et al, who conducted an online survey of GPs and practice managers in the East Midlands during May and June 2020 to explore how practices were coping with the pandemic. 12 They found practices implementing a similar range of measures, to both buildings and processes, to make face-to-face contact possible.…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
“…Avoid assuming that a COVID-19 death is inherently bad or worse than a typical death Since media narratives affect the public, people's fears, concerns and anxieties are likely to arise from media messaging. Negativity and lack of nuance were found in a study of media coverage of remote medical consultations during the pandemic 47 ; we found similar features in coverage of death and bereavement. The lack of positive advice for those affected, or examples of a 'good enough' death, may further stoke anxieties and reduce health-seeking behaviours.…”
Section: Implications Rationalesupporting
confidence: 77%